Crime in Japan: A Psychological Perspective - Bui, Laura (Palgrave Advances in Criminology and Criminal Justice in Asia, 2019)
1. Introduction -- 2. Culture -- 3. Life Course -- 4. Family -- 5. Youth -- 6. School -- 7. Mental Disorders -- 8. Biosocial Interactions -- 9. Conclusions